2004
DOI: 10.2337/diabetes.53.2.347
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Impairs Insulin Signaling in Rat Adipocytes

Abstract: Leptin modulates glucose homeostasis by acting as an insulin-sensitizing factor in most insulin target tissues. Nevertheless, insulin-dependent glucose uptake in white adipose tissue decreases after in vivo treatment with leptin. Moreover, elevated leptin concentrations inhibit insulin metabolic effects in adipocytes. Here we studied both, direct and centrally mediated effects of leptin on insulin signaling in rat adipocytes. Adipocyte incubation with low leptin concentrations did not modify the insulin stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 57 publications
(75 reference statements)
4
80
0
5
Order By: Relevance
“…In several recent studies, it has also been shown that leptin has a profound inhibitory influence upon insulin secretion by acting directly on the pancreatic betacells (Jaworek et al 2003;Perez et al 2004). In most overweight individuals, however, physiological regulation of body weight by leptin seems to be disturbed, representing "leptin resistance."…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In several recent studies, it has also been shown that leptin has a profound inhibitory influence upon insulin secretion by acting directly on the pancreatic betacells (Jaworek et al 2003;Perez et al 2004). In most overweight individuals, however, physiological regulation of body weight by leptin seems to be disturbed, representing "leptin resistance."…”
Section: Resultsmentioning
confidence: 99%
“…Leptin was first described to act on the satiety center in the hypothalamus through specific receptors to restrict food intake and enhance energy expenditure (Konturek et al 2001). It has also been demonstrated that leptin has some peripheral effects such as inhibition of insulin biosynthesis and secretion in pancreatic beta-cells (Jaworek et al 2003;Benomar et al 2004;Perez et al 2004). In most overweight individuals, however, physiological regulation of body weight by leptin seems to be disturbed, representing "leptin resistance."…”
Section: Discussionmentioning
confidence: 99%
“…Five-and 21-month-old rats were randomly selected to undergo a food restriction protocol as described earlier (Pérez et al 2004). They were placed in individual cages and fed daily 18 and 21 g of chow respectively (equivalent to z80% of normal food intake).…”
Section: Food Restrictionmentioning
confidence: 99%
“…Los estudios en ratones knock out para el gen de leptina demostraron una asociación entre leptina, obesidad y otras secuelas metabólicas, tales como hiperfagia e hiperglucemia (16,17); posteriormente, se realizaron diversos estudios que, además de asociarla con obesidad tanto en humanos como en ratas, la relacionan con cambios en las concentraciones y expresión de la insulina, lo cual podría explicar la fisiología y patología de la diabetes mellitus no insulino dependiente en la obesidad (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35); algunos de estos estudios sustentan sus conclusiones en lo siguiente: 1) Durante la pérdida de peso se observan disminuciones en la leptina con reducción en las concentraciones de insulina e independientemente de los cambios de adiposidad (21,26).…”
unclassified
“…4) En las ratas Wistar con concentraciones plasmáticas elevadas de leptina se inhibe la señalización ejercida por la insulina en el adipocito al dañar el proceso de autofosforilación de su receptor, lo anterior parece estar relacionado con el incremento en la expresión de la proteína SOCS-3 (31).…”
unclassified